Penerapan Metode VIKOR Dalam Pemilihan Siaran Radio Terbaik - Fitriani, Fitriani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
In a series of broadcast regulatory processes from the State through the Regional Indonesian Broadcasting Commission to be able to provide an assessment of whether a broadcasting institution is appropriate to provide its broadcasts and not deviate from its mission of providing information to the public Therefore radio is one of the broadcasts of government programs to obtain information directly in the form of a public and open voice. Because radio is one of the oldest electronic mass media and has become an important part of the history of the development of communication technology. Decision support system (DSS) refers to a system that utilizes computers in the decision-making process to get consistent decision results. In this study the author applies Vise Kriterijumska Optimizacija Kompromisno Resenje in Serbia (VIKOR) as a method to be applied in decision support system applications. The VIKOR method is part of the Multi-Attibut Decision Making (MADM) Concept, which requires normalization of the calculations. The expected results in this study can obtain the maximum decision